EVALUATION OF PREVALENCE OF ANDREWS’ KEYS: CROWN ANGULATION, CROWN INCLINATION AND CURVE OF SPEE IN BIHAR POPULATION - Dr Lalima Kumari; Dr Anurag Rai; Dr Kamal Nayan (The Bioscan, 2025)
Objectives: Given the widespread use and dissemination of the concepts of Andrews' six occlusion keys as a tool for diagnosis and treatment planning, it becomes necessary to establish the norms for every ethnic group as Caucasian norms show a great degree of variation when applied to different populations. Aim: To evaluate the prevalence of three Keys; key II (Crown angulation), key III (Crown inclination) and key VI (curve of Spee) in a sample population from Bihar having occlusion near normal. Methodology: 100 study models from Bihar population with natural normal occlusion were studied. The frequency with which the three keys: Key II, Key III and Key VI were found in everyone was observed, as well as which keys were most and least frequent. Statistical analysis: SPSS software and various analytic tools were used to evaluate the data. Results and Conclusions: The evaluation of the prevalence of the three keys of Andrews optimal occlusion in Bihar population showed a prevalence rate of 96 percent for curve of Spee, second most prevalent being crown inclination with a prevalence rate of 90.25 percent whereas a prevalence rate of 84.71 percent was found for crown angulation. Thus, it can be concluded that most people in the Bihar population closely follow Andrews’ norms particularly for the key IInd, IIIrd and VIth.